2019
DOI: 10.1021/acs.nanolett.8b03764
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Intracellular Delivery of Single Particles in Single Cells by 3D Hollow Nanoelectrodes

Abstract: Delivery of molecules into intracellular compartments is one of the fundamental requirements in molecular biology. However, the possibility of delivering a precise number of nano-objects with single-particle resolution is still an open challenge. Here we present an electrophoretic platform based on 3D hollow nanoelectrodes to enable delivery of single nanoparticles into single selected cells and monitoring of the single-particle delivery by surface-enhanced Raman scattering (SERS). The gold-coated hollow nanoe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 75 publications
0
64
0
Order By: Relevance
“…In a report from the same group, Huang et al used gold‐coated nanostraws, coupled with electroporation to deliver Raman‐tagged gold nanorods into fibroblast cells (NIH‐3T3) with single‐particle precision ( Figure ) . Surface‐enhanced Raman scattering from the gold nanorods, plus shielding from the delivery reservoir by the gold‐coated nanostraw layer, means single nanorods could be visualized as a momentary increases in the Raman signal as they passed through the nanostraw.…”
Section: Biochemical Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report from the same group, Huang et al used gold‐coated nanostraws, coupled with electroporation to deliver Raman‐tagged gold nanorods into fibroblast cells (NIH‐3T3) with single‐particle precision ( Figure ) . Surface‐enhanced Raman scattering from the gold nanorods, plus shielding from the delivery reservoir by the gold‐coated nanostraw layer, means single nanorods could be visualized as a momentary increases in the Raman signal as they passed through the nanostraw.…”
Section: Biochemical Sensingmentioning
confidence: 99%
“…Raman correlation spectroscopy was used to track surface‐enhanced Raman scattering from single gold nanorods passing through the nanostraws. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Biochemical Sensingmentioning
confidence: 99%
“…The microfluidic embedded platform performs as nanoelectrodes for cell electroporation, nanochannels for electrophoretic delivery, as well as plasmonic antennae. [ 17 ]…”
mentioning
confidence: 99%
“…With this strategy, Messina et al reported a hollow plasmonic gold nanotube‐based platform for delivery of a wide variety of cargo into the cell interior with prominent advantages such as single‐cell resolution and the potential of multiplexed applications (Figure 10b). [ 51 ] Moreover, single nanoparticles could also be delivered into single cells of choice using these optoporation‐enhanced hollow gold nanotubes, [ 169 ] thus achieving a new level of delivery precision.…”
Section: Assisted Penetrationmentioning
confidence: 99%